PALEOENVIRONMENTAL SIGNIFICANCE OF SEDIMENTARY STRUCTURES IN THE CAMPANO-MAASTRICHTIAN SUCCESSION IN THE GONGOLA BASIN NE NIGERIA - Hamidu, Ibrahim (BIMA JOURNAL OF SCIENCE AND TECHNOLOGY GOMBE, 2017)
The pre and post depositonal sedimentary structures have been examined, recorded and interpreted from the foreshore-shoreface and alluvial facies of the Campano-Maastrichtian succession in the Gongola Basin. Some of these structures seem to be diagnostic of the environment, depositional processes, conditions and direction of the water current which deposited the sediments. The upper Fika Formationis dominantly shale with bioturbatedooidal ironstone toward the top, which indicates deposition mainly from suspension andthe bioturbatedooidal ironstones form in agitated water as water depth decreased, increased agitation formed clay ooids and moderate to intense bioturbation by Thalassinoides, OphiomorphaandSkolithos.as water depths subsequently increased and finaly replacement of kaolinitic precursors with iron oxides/hydroxides.Thetrace fossil assemblage Thalassinoides, Ophiomorpha and Skolithosare consistent with a shallow marine setting.Their presence indicates littoral and shallow sub-littoral environments. The Arowa Formation is made up of cycles that are coarsening-upward and contains channel-filling sandstones in the lower part. The lower shale-dominated part of the cycles contain interbedded sandstones and shales in which hummocky cross stratification, ripples and trace fossils Thalassinoides, Skolithos, Ophiomorpha, and Planolitesoccur. The sandstone-dominated portion of the Arowa Formation are mainly parallel laminatedand dip gently (2o– 3o) seaward. The main sedimentary structure of the DuguriFormation, is cross-bedded sandstone overlying a basal conglomerate/pebbly sandstone. The paucity of argillaceous horizons suggests deposition in braided rivers.